(untitled) (Journal of the College of Basic Education, 2026)
This research revolves around a person’s negative thinking, his dark view of things, pessimism, and abstention from work and achievement, and its most prominent manifestations are the negativity of religiosity and negativity with oneself, and addressing this regressive state that distances a person from his civilized role in this life through the cognitive implications of subservience, represented by subservience of God Almighty. The universe belongs to him with all that it contains of heaven and earth and all the blessings of God Almighty emanating in the vast universe, as well as his subjugation of himself to him mind, heart and soul. The human mind is the greatest thing that God Almighty created and bestowed on mankind, and through it he is able to benefit from the blessings of God subservient to him to get out of... Negative thinking and shifting towards positive, optimistic thinking filled with the spirit of hope, life, achievement and progress.